The Evolution of Nonprofit Governance Research: Reflections, Insights, and Next Steps. (April 2023) - Renz, David O.; Brown, William A.; Andersson, Fredrik O.
The literature on nonprofit governance and boards has grown substantially during the past 50 years as researchers from a variety of disciplines and fields have studied governance systems and processes to examine how they are organized, the practices they employ, and their relations with and impacts on nonprofits. This essay offers a domain-based narrative review of the research on the governance of nonprofit organizations and how it has developed over these 50 years. Building on literature reviews and a Delphi study, we summarize the progression of nonprofit governance research, employ a multi-dimensional framework to summarize and assess the state of the field, and offer recommendations for future study. We find the increasingly multinational and multicultural literature of the field has become more rich, nuanced, and increasingly inclusive of contingency, complexity, paradox, and the diverse theoretical perspectives that will enhance our understanding of nonprofit governance.